2016
DOI: 10.1161/jaha.115.002993
|View full text |Cite
|
Sign up to set email alerts
|

Two C‐C Family Chemokines, Eotaxin and RANTES, Are Novel Independent Plasma Biomarkers for Abdominal Aortic Aneurysm

Abstract: BackgroundInflammation of the aortic wall is recognised as a key pathogenesis of abdominal aortic aneurysm (AAA). This study was undertaken to determine whether inflammatory cytokines could be used as biomarkers for the presence of AAA.Methods and ResultsTissue profiles of 27 inflammatory cytokine were examined in AAA (n=14) and nonaneurysmal (n=14) aortic tissues. Three cytokines, regulated upon activation normally T‐cell expressed and secreted (RANTES), eotaxin, and macrophage inflammatory protein 1 beta (MI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
25
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 39 publications
3
25
0
Order By: Relevance
“…Elevated expression of CCR5 in PVT containing CD4 + and CD8 + cells as well as a differential expression of these cells between AAA wall and PVT (seen for CD4 + T cells) provides a hint for the role of RANTES chemokine in T cell recruitment to PVT and AAA wall. This data, coupled with the fact that RANTES is upregulated within the adventitia of human AAA (8) may suggest a role for this chemokine in the regulation of T cell trafficking in AAA, which has been demonstrated in relation to many other risk factors of AAA such as hypertension (50). Furthermore, angiotensin II induced expression of RANTES within the vasculature and CCR5 on T cells is thought to mediate T cell accumulation within the PVAT and adventitia in a mouse model of hypertension (47) indicating the importance of this chemotactic axis in both mice and humans.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Elevated expression of CCR5 in PVT containing CD4 + and CD8 + cells as well as a differential expression of these cells between AAA wall and PVT (seen for CD4 + T cells) provides a hint for the role of RANTES chemokine in T cell recruitment to PVT and AAA wall. This data, coupled with the fact that RANTES is upregulated within the adventitia of human AAA (8) may suggest a role for this chemokine in the regulation of T cell trafficking in AAA, which has been demonstrated in relation to many other risk factors of AAA such as hypertension (50). Furthermore, angiotensin II induced expression of RANTES within the vasculature and CCR5 on T cells is thought to mediate T cell accumulation within the PVAT and adventitia in a mouse model of hypertension (47) indicating the importance of this chemotactic axis in both mice and humans.…”
Section: Discussionmentioning
confidence: 81%
“…The mechanisms of AAA, defined primarily in animal model studies, are complex, involving smooth muscle cell apoptosis, oxidative stress (4), and inflammation (5). Clinically, patients with AAA have elevated circulating pro-inflammatory cytokines (68) and immunohistochemical studies of AAA reveal the presence of inflammatory cells such as macrophages, T cells, B cells, dendritic cells, natural killer cells, neutrophils, and mast cells (914).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study suggested eotaxin to be an independent plasma biomarker for AAA [24]. Moreover, eotaxin has been reported to induce pro-MMP2 expressions in VSMCs [25].…”
Section: Resultsmentioning
confidence: 99%
“…Eosinophil chemoattractant Plays a role in the pathogenesis of several allergic conditions (e.g. asthma) (Williams, 2015) Increased in eosinophilic myocarditis (Diny et al, 2016), abdominal aortic aneurysms (Jones, Phillips, Williams, van Rij, & Kabir, 2016) and CAD (Economou et al, 2001).…”
Section: ) Ccl11mentioning
confidence: 99%